PERSEPSI MASYARAKAT TERHADAP HUTAN KOTA SEBAGAI RUANG TERBUKA HI JAU PUBLIK KASUS HUTAN KOTA DI KABUPATEN KETAPANG KALIMANTAN BARAT - , HERMILA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Urban forest is one form of green open spaces and it is very important for a city because of it many roles and benefits. Such roles anclude: among others as a place to play, exercise, relax, to get some fresh air and means of recreation. The Government's efforts in providing urban forest is not only determined by the availability of funds but also the participation and support of the community It is , therefore, very important to consider public views on the existence of the urban forest. The purpose of this study is to investigate public perception in the village Tengah and village Sukaharja of the urban forest as a public green open space and what factors affecting such perceptions. This research was conducted in West Kalimantan Ketapang. The research method used has deductive quantitative-qualitative. Primary data collected from interviews, field observation and questionnaires via random sampling technique. Data in this study were statistically analyzed using frequencies and cross tabulation (crosstabs), then performed using the Chi square test of independence and correlation coefficient using SPSS. 17.0 to see the significance of the relationship between variables of the study. The research found that there are differences in public perception of urban forest as a public green open space. People in located the urban center, understanding and illustration of green open space which is already very good, while communities around the urban forest, understanding and description of space existing green open still not good. Factors that influence public perceptions in the city center are : education level, occupation, income and the amount of information has been received. While factors that affect the public perception around the urban forest are: level of education , the magnitude of income and the information has been received. In addition, differences is characteristics of regions and communities also affects public perception. Local governments has to support the existence of the urban forest by involving the community to participate in its management. It is very important to provide information about the existence of urban forest. Dissemination of information techniques should be adjusted to the conditions and characteristics of the local community.